Managing and Controlling the Work of Wet Nurses: Notes from a Register of Nursemaids of the ‘Ospedale Maggiore’ in Milan (15th century) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
this paper aims to provide a better understanding of how the Ospedale Maggiore of Milan managed the problem of child abandonment at the end of 15th century. the oldest register kept in the Archivio degli Istituti Provinciali (Milan) provides important information concerning the role played by wet nurses and the way in which they were recruited, thus representing a crucial source for scholars engaged in this field.
Keywords: Ospedale Maggiore of Milan; child abandonment; wet nurses; Archivio degli Istituti Provinciali of Milan; 15th century